2019
DOI: 10.3390/plants8080284
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Physcomitrella patens Glycerol-3-Phosphate Acyltransferase 9 and an Increase in Seed Oil Content in Arabidopsis by Its Ectopic Expression

Abstract: Since vegetable oils (usually triacylglycerol [TAG]) are extensively used as food and raw materials, an increase in storage oil content and production of valuable polyunsaturated fatty acids (PUFAs) in transgenic plants is desirable. In this study, a gene encoding glycerol-3-phosphate acyltransferase 9 (GPAT9), which catalyzes the synthesis of lysophosphatidic acid (LPA) from a glycerol-3-phosphate and acyl-CoA, was isolated from Physcomitrella patens, which produces high levels of very-long-chain PUFAs in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…LPA or phatidylcholine (PC) are further catalyzed by a series of enzymes, including diacylglycerol acyltransferase (DGAT) and phospholipid diacylglycerol acyltransferase (PDAT), and finally form TAG ( Figure 2 ). Studies have shown that GPAT [ 28 ], DGAT [ 29 , 30 , 31 ] and PDAT [ 30 ] directly affect the TAG synthesis. Transcription factors of AtMYB89 [ 32 ], AtMYB96 [ 33 ], LEC [ 34 , 35 , 36 , 37 ],GL2 [ 38 , 39 ], FUS3 [ 40 ] and HB2 [ 41 ] are involved in TAG biosynthesis regulation.…”
Section: Identification Of Maize Potential Gene Resources For Oil Con...mentioning
confidence: 99%
“…LPA or phatidylcholine (PC) are further catalyzed by a series of enzymes, including diacylglycerol acyltransferase (DGAT) and phospholipid diacylglycerol acyltransferase (PDAT), and finally form TAG ( Figure 2 ). Studies have shown that GPAT [ 28 ], DGAT [ 29 , 30 , 31 ] and PDAT [ 30 ] directly affect the TAG synthesis. Transcription factors of AtMYB89 [ 32 ], AtMYB96 [ 33 ], LEC [ 34 , 35 , 36 , 37 ],GL2 [ 38 , 39 ], FUS3 [ 40 ] and HB2 [ 41 ] are involved in TAG biosynthesis regulation.…”
Section: Identification Of Maize Potential Gene Resources For Oil Con...mentioning
confidence: 99%
“…Yang et al [20] studied the metabolism of membrane lipid synthesis of Physcomitrella patens, a moss corresponding to early-stage plants during the terrestrial evolution of plants. The haploid cells of P. patens, protonema, and gametophore, have a high content of 65% of the long-chain polyunsaturated fatty acid (LC-PUFA) and a very-long-chain-PUFA [21][22][23].…”
Section: Highlight Of Special Issuesmentioning
confidence: 99%
“…The GPAT gene family has been identified in many model plants, including Arabidopsis thaliana [ 8 , 10 ], Brassica napus [ 11 ], Oryza sativa [ 10 ], Zea mays [ 12 ], and other plants, such as Paeonia [ 13 ], Gossypium [ 14 ], and Perilla frutescens [ 15 ]. It has been confirmed that the members of the GPAT gene family have been widely described for their role in male fertility [ 16 , 17 , 18 , 19 , 20 , 21 ], seed development [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], biotic and abiotic stress tolerance [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], and cuticle or suberin production [ 5 , 22 , 44 , 45 , 46 , 47 , 48 , 49 ]. At present, the research on the GPAT gene family is the best in the model plant Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%